Strategi Efektif dalam Pengembangan Literasi dan Numerasi Siswa SD Kelas V: Bahasa Indonesia - Suryadi, Angga; Kadek Ananda Pratiwi; Putra, I Putu Risky Ardana; Yani, Ketut Candra; Mirayani, Komang; Werang, Basillius Redan (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
This study explores effective strategies in developing literacy and numeracy of grade V elementary school students in Indonesia. The research method uses a literature study that analyzes various articles, books, and reports related to government policies on strengthening literacy and numeracy. The data sources in this study come from scientific journals, reference books, research reports, and relevant government policy documents. The data collection technique involves searching literature through academic databases, digital libraries, and official government websites. Data analysis is carried out using the content analysis method, where the collected data is categorized and evaluated to identify key themes and effective strategies. The results showed that project-based teaching methods, thematic learning, and the use of educational technology can significantly improve students' literacy skills. In addition, problem-based learning methods, contextual learning, and the use of educational games and manipulative aids are effective in increasing student numeracy. Teacher training and professional development as well as government policy support such as the National Literacy Movement, School Literacy Movement, Minimum Competency Assessment, and Merdeka Belajar curriculum also play an important role in the success of these strategies. The excellence of this article lies in the comprehensive analysis and integration of various innovative teaching strategies, as well as the emphasis on ongoing policy support. In conclusion, continuous support from various parties is needed to ensure the improvement of the quality of student literacy and numeracy education in Indonesia.